Cybersecurity Laboratory Education Research: A Lush Ecosystem or Elephant Graveyard? (Journal of The Colloquium for Information Systems Security Education, 2022)
Is cybersecurity laboratory education research a lush ecosystem or an elephant graveyard? The value of such a question cuts to the health of a research field. Further, the health of a research field stems from the lineage of work extending into the past and present. In other words, mature and robust fields of knowledge exhibit interlinked research with dense pockets of follow-up. In contrast, nascent or limited fields lack such linking or association measurable by the frequency of new research extended results. These interlinks and associations are indeed quantifiable through the meta-study of bibliometrics. In fact, prior research discovered that only thirty percent of computer science research - a strongly related field - are extended after publication. However, no work to date has examined cybersecurity laboratory education for the same phenomenon. To that end, this work evaluated 400 articles with the goal of ascertaining to what degree three operationalized follow-up categories occur in the literature. The results indicate 62.5% of articles do not extend existing research. The conclusions and recommendations included at the end of this work offer potential insights into why cybersecurity
Keywords: cybersecurity education; pedagogy; laboratories; bibliometrics